Influence of technical parameters on epicardial fat volume quantification at cardiac CT. Issue 6 (June 2015) - Bucher, Andreas M.; Joseph Schoepf, U.; Krazinski, Aleksander W.; Silverman, Justin; Spearman, James V.; De Cecco, Carlo N.; Meinel, Felix G.; Vogl, Thomas J.; Geyer, Lucas L.
Highlights: Upper threshold levels and contrast enhancement influence epicardial fat volumetry. Cardiac cycle does not significantly influence epicardial fat volumetry. Adjustments of upper threshold can lead to comparable volumetry results. Abstract: Objectives: To systematically analyze the influence of technical parameters on quantification of epicardial fat volume (EATV) at cardiac CT. Methods: 153 routine cardiac CT data sets were analyzed using three-dimensional pericardial border delineation. Three image series were reconstructed per patient: (a) CTAD : coronary CT angiography (CTA), diastolic phase; (b) CTAS : coronary CTA, systolic phase; (c) CaScD : non-contrast CT, diastolic phase. EATV was calculated using three different upper thresholds (−15HU, −30HU, −45HU). Repeated measures ANOVA, Spearman's rho, and Bland Altman plots were used. Results: Mean EATV differed between all three image series at a −30HU threshold (CTAD 87.2 ± 38.5 ml, CTAS 90.9 ± 37.7 ml, CaScD 130.7 ± 49.5 ml, P  < 0.001). EATV of diastolic and systolic CTA reconstructions did not differ significantly ( P  = 0.225). Mean EATV for contrast enhanced CTA at a −15HU threshold (CTAD15 102.4 ± 43.6 ml, CTAS15 105.3 ± 42.3 ml) could be approximated most closely by non-contrast CT at −45HU threshold (CaScD45 105.3 ± 40.8 ml). The correlation was excellent: CTAS15 –CTAD15, rho = 0.943; CTAD15 –CaScD45, rho = 0.905; CTAS15 –CaScD45, rho = 0.924; each P  < 0.001). Bias values from Bland Altman Analysis were: CTAS15 –CTAD15, 4.9%; CTAD15 –CaScD45, −4.3%; CTAS15 –CaScD45, 0.6%. Conclusions: Measured EATV can differ substantially between contrast enhanced and non-contrast CT studies, which can be reconciled by threshold modification. Heart cycle phase does not significantly influence EATV measurements.